SERAT KULIT KAYU BAHAN SANDANG: KEANEKARAGAMAN JENIS DAN PROSPEKNYADI INDONESIA - Rahayu, Mulyati; Sihotang, Vera Budi Lestari (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Indonesia has known to have several fiber plants used as rope, craft and clothing material. The literature study, observations well as interview with local community in several places in Sumatra, Kalimantan, Moluccas and Sulawesi suggested that there were nine fiber plant species that were used as clothing material in the past. But clothing material from the bark of Broussonetia papyrifera (L.)L?Her. ex Vent.,?kumpe?, is still being fabricated and used in Cental Sulawesi up to now.Two of those nine fiber plant species for clothing material had good economic value namely Boehmeria nivea (L.) Gaudich and Broussonetia papyrifera (L.) L?Her. ex Vent.